FAKTOR-FAKTOR YANG MENGHAMBAT PEMANFAATAN ADOPSI LAYANAN E-LEARNING DI UNIVERSITAS PAPUA : INNOVATION RESISTANCE THEORY (IRT): FACTORS THAT OBSTRUCT THE USE OF ADOPTION OF E-LEARNING IN UNIVERSITY OF PAPUA : INNOVATION RESISTANCE THEORY (IRT) - Argi Dwi Raga Febriarman; Dedi I Inan; Fridolin F Paiki (Universitas Papua, 2023)
E-learning is an online learning service that can help and support the student lecture process. Since e-learning was first created at the University of Papua, until now there has been no specific research examining the adoption of e-learning utilization. Therefore, this study aims to determine the factors that hinder the adoption of the use of e-learning at the University of Papua using the IRT theory (Usage Barrier, Tradition Barrier, Perceived Cost Barrier) and combined with external variables Perceived Ease Of Use (PEOU) and Facilitating Conditions (FC) as measured by Structural Equation Modeling-Partial Least Square (SEM-PLS). Questionnaires were distributed to students using e-learning at the University of Papua. A total of 263 respondents were obtained in distributing questionnaires for almost two months. From the results of this study it was found that tradition barriers and perceived cost barriers were inhibiting factors for the adoption of e-learning utilization and had no positive effect, while usage barriers, perceived ease of use and facilitating conditions had a positive influence on e-learning adoption.